PENGARUH JENIS PAKAN TERHADAP PRODUKSI TELUR JANGKRIK (Gryllus miratus) - Fitriani, Rini - (Pendidikan Biologi, 2014)
Feed is very important to be considered in the cultivation of crickets. Crickets like the fresh feed so that the number of eggs produced will be maximized with good quality. Breeders do not know the good feed to crickets yet. Based on the researchabove has been done with the aim to know the effect of feed of egg crickets production (Gryllus miratus). This research was conducted in Asahanjorong kampung PalakNagariPasir Talang Kecamatan Sungai Pagu Kabupaten solok selatan, in August 2014. The method used in this research is completely randomized design with 5 treatments and 5 replications namely A: voor 311, B: leaf chicory , C: kale leaves, D: green cabbage leaves, and E: spinach leaves. The materials used in this study were 150 head crickets, where each treatment added with tailed crickets. Data were analyzed variation and shows than will be tasted, byused BNT.Theresult of this research shows that the average number and weight of eggs that highes on chicory treatment. Feed that very effective to produce eggs and weight of eggs is chicory leaves.